2014
DOI: 10.1080/02687038.2014.988110
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis from a novel treatment targeting the exchange of new information within storytelling for people with nonfluent aphasia and their partners

Abstract: UWE makes no representation or warranties of commercial utility, title, or fitness for a particular purpose or any other warranty, express or implied in respect of any material deposited. UWE makes no representation that the use of the materials will not infringe any patent, copyright, trademark or other property or proprietary rights. UWE accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…Rautakoski, 2011aRautakoski, , 2011b, family therapy (n=3) (Nichols et al, 1996;Borenstein et al, 1987;Währborg & Bohrenstein, 1989), or unique name/ features e.g. learner-centred conversation training programme (n=2) (Sorin-Peters, 2004; Sorin-Peters & Patterson, 2014), interactive storytelling therapy (n=1) (Carragher et al, 2015) and conversational coaching (n=1) (Hopper et al, 2002). Many however were unspecified, using a range of terms: conversational treatment, communication partners, conversation partners therapy, conducting conversation, aphasia couples therapy, solution focused aphasia therapy, recognition training, multimodality communication, therapy using conversation analysis, and combining neuropsychology and pragmatic approaches; and structured/ psycho-education programme for carers, residential family based intervention, group communication training for carers, and (social) support course/ group.…”
Section: Narrative Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Rautakoski, 2011aRautakoski, , 2011b, family therapy (n=3) (Nichols et al, 1996;Borenstein et al, 1987;Währborg & Bohrenstein, 1989), or unique name/ features e.g. learner-centred conversation training programme (n=2) (Sorin-Peters, 2004; Sorin-Peters & Patterson, 2014), interactive storytelling therapy (n=1) (Carragher et al, 2015) and conversational coaching (n=1) (Hopper et al, 2002). Many however were unspecified, using a range of terms: conversational treatment, communication partners, conversation partners therapy, conducting conversation, aphasia couples therapy, solution focused aphasia therapy, recognition training, multimodality communication, therapy using conversation analysis, and combining neuropsychology and pragmatic approaches; and structured/ psycho-education programme for carers, residential family based intervention, group communication training for carers, and (social) support course/ group.…”
Section: Narrative Synthesismentioning
confidence: 99%
“…Small group sizes and group provision were believed to maximise peer learning and support, and joint problem-solving (Hinckley & Packard, 2001;Purdy & Hindenlang, 2005). To facilitate generalisation to everyday use, Carragher et al (2015) outlined four essential or active ingredients that were hypothesized to contribute to generalisation of behaviours to untrained tasks, which was the motivation for their study.…”
Section: Tidier Item 2: Why: "Describe Any Rationale Theory or Goalmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies on discourse intervention that we found comprised three distinct approaches to the improvement of discourse (in some studies, more than one approach is used). One approach targets word and sentence production (simple and complex clauses) within discourse [56,[70][71][72][73][74]; another involves massed practice of whole discourses, using AphasiaScripts [75][76][77] and a third focuses on supporting participants to improve their discourse macrostructure using story grammar [56,64,68,78]. Overall, the findings from these studies were positive, with clients' improving in language use, the amount and quality of information conveyed, and how the information was structured, although it was not the case that all three elements improved in every case.…”
Section: Discourse Therapy For Adults With Aphasiamentioning
confidence: 99%
“…The wider impact of our interventions, such as those related to increased participation or improved self-esteem, are viewed here outside the realm of generalisation although are considered no less important to evaluating aphasia interventions. The framework proposed within this paper distinguishes between therapies that target a single level (as in the papers of Croot et al and Kiran et al), and those that target multiple linguistic levels (as in Edmonds, Obermeyer, & Kernan, 2015;Whitworth et al, 2015;and Carragher, Sage, & Conroy, 2015). The literature is then reviewed in terms of whether the focus of therapy is on single words (as in Croot et al), sentences (Kiran et al), single words and sentences (Edmonds et al) or single words, sentences and discourse (Whitworth et al and Carragher et al).…”
mentioning
confidence: 99%